Life Quality Of End Of Life Patient's Family in Intensive Care Units - Noor Fitriyani; Reni Sulung Utami; Achmad Zulfa Juniarto (Alma Ata University Press, 2018)
Fifty percent of end-of-life patients spend the last time of their life in the Intensive Care Unit (ICU). End of life conditions have an impact on the psychological, physical, social, and family environment that affect the quality of life of other families. Family welfare will have an impact on care outcomes, hospitalization time, and patient stressor levels. The purpose of this study was to explore the life quality of end of life patient's family in ICU. This research used qualitative method with descriptive phenomenology approach. Sampling was done by purposive sampling technique with 9 participants. data were collected through in-depth interviews and analyzed using the Colaizzi method. The data validity was designed to meet the principle of triangulation of researchers and theory. The results showed 7 dimensions of life quality of end of life patient's family of physical health (fatigue, sleep disorder, headache, decreased appetite), mental health (anxiety, sadness, hope of improved family health condition), spiritual health (acceptance), health social (social support), daily life (daily life adjustment), financial health (financial burden), and environment (opportunity to get information, family infrastructure). This study concludes that end of life condition of critical patients impacts on the 7 dimensions of family life quality. Nurses should pay attention to the family life quality because it affected the condition of the patient and family as the care service unit. Keywords: Life Quality, Family, End Of Life, Intensive Care Unit